2014
DOI: 10.1371/journal.pone.0109775
|View full text |Cite
|
Sign up to set email alerts
|

Functional Phenotype of Synovial Monocytes Modulating Inflammatory T-Cell Responses in Rheumatoid Arthritis (RA)

Abstract: Monocytes function as crucial innate effectors in the pathogenesis of chronic inflammatory diseases, including autoimmunity, as well as in the inflammatory response against infectious pathogens. Human monocytes are heterogeneous and can be classified into three distinct subsets based on CD14 and CD16 expression. Although accumulating evidence suggests distinct functions of monocyte subsets in inflammatory conditions, their pathogenic roles in autoimmune diseases remain unclear. Thus, we investigated the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 35 publications
3
88
1
Order By: Relevance
“…We previously reported that synovial monocytes possess the unique capability to promote Th1 and Th17 responses of peripheral CD4 T cells (17). Although the higher expression of surface B7-H3 was described as one of major features of synovial monocytes in the studies, we also showed the enhanced expressions of HLA-DR and CD80, which delivers "signal 1" and "signal 2" to T cells, respectively.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We previously reported that synovial monocytes possess the unique capability to promote Th1 and Th17 responses of peripheral CD4 T cells (17). Although the higher expression of surface B7-H3 was described as one of major features of synovial monocytes in the studies, we also showed the enhanced expressions of HLA-DR and CD80, which delivers "signal 1" and "signal 2" to T cells, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…1, A and B) (17). To confirm our microarray data in a secondary cohort, CD14 ϩ monocytes were purified from PBMCs and SFMCs, which were prepared simultaneously from the same RA patients, and B7-H3 expression was analyzed using RT-PCR and flow cytometry.…”
Section: B7-h3 Expression Is Markedly Elevated On Synovialmentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, alterations in the composition of the mobile CSF monocyte pool may reflect a shift of CD16 + monocytes from the periphery to sites of inflammation. Such a compartmentalization, which is typical for MS, may account for the difference in monocyte subgroup distributions in other autoimmune diseases (7)(8)(9)(10)(11)(12)(13)(14)(15). CD16 + non-classical so-called patrolling monocytes exert important functions in the peripheral immune compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was demonstrated that the expansion of CD16 + monocytes is driven by the intermediate monocyte subset (9)(10)(11) and that these CD16 + monocytes actively shape T cell responses by favoring Th17 differentiation (9). Accordingly, it has been suggested that CD16 + monocytes play a pivotal role in the pathophysiology of autoimmune diseases.…”
mentioning
confidence: 99%